(untitled) (Communication & Society, 2013)
The h-index is a research impact and productivity indicator proposed by Hirsch (USA, 2005) and adopted by WoK and Scopus. However, it was not recognised in Communication until Google entered into the field of bibliometry in 2012 by introducing h-impact lists of scientific journals and h-index on scholars’ profiles. This article compares the h-index and the impact factor, identifies the context indicators (g, m, h5, i10), tries to define a reference hR index for the Communication field and analyses the h-impact of journals in this field in the Ibero-American region.